A rare case of self‐healing giant condyloma acuminatum. Issue 1 (17th November 2021) - Jin, Shuang; Liu, Linxi; Li, Rong; Zhou, Xuyue; Wang, Ziwei; Luan, Chao; Chen, Kun; Huang, Dan
Abstract: Giant condyloma acuminatum (GCA) which is also called Buschke‐Lowenstein tumor. It is a rare tumor of the anorectal area and external genitalia associated with low‐risk HPV types 6 or 11. GCA has a high‐rate of recurrence (66%) and malignant transformation (56%). The clinical features of GCA are progression of exophytic, ulcerative, and cauliflower‐shaped tumors, it has significant dimensions and may undergo malignant transformation such as squamous cell carcinoma or cervical cancer. It is difficult to treat GCA, and it may be impossible for GCA to self‐healing, but we herein report a rare case of a 19‐year‐old female with self‐healing GCA.